SOCIAL AND CREATIVE INDUSTRIES IN THE DEVELOPMENT OF THE CONCEPT OF SMART CITIES (Economic journal of Lesya Ukrainka Volyn National University, 2019)
Introduction. The article analyzes the categories of "smart city" and "creative industries" as an innovative vector for the development of the region and obtain social and economic effect. The level of development of this problem is clarified among the theoretical and practical approaches, the experience of the European Union, America in the implementation and implementation of the concept of "smart city" is presented. An excursion of theoretical and methodological tools of the "creative industries" is made and their role in the strategy of development of "smart cities" of the region is outlined. The basic directions of realization of the concept of "smart cities" are defined. The practice of financing the European Union's leading cities in the concept of "smart cities" is explored, in particular for modernization, improvement of energy efficiency of buildings and transport networks, smart energy management and consumption, introduction of a new model of information and communication, development of the service sector. The purpose of the article. The originality of the study is related to the substantiation of theoretical hypotheses regarding the main directions of synthesis of creative industries, as the driving force behind the concept of "smart cities". The results of the analysis will bring Ukrainian cities closer to the European centers of information and cultural industries of the region. The role of prestigious industries in the concept of "smart cities" of Ukraine is considerable, but it can be realized under the following circumstances: psychological perception of cultural and social industries by creative economy measures; theoretical and practical studies of the topic of cultural innovation and "smart cities", which have been presented in literary sources; improving the symbiosis of lawmaking, financial levers, further mechanism for the development of "smart cities" and cultural and creative industries; increase of specialists of creative sphere, sufficiency of information and communication sources, etc., etc. Therefore, in the arena of inter-regional competition, a special place belongs to the concept of creating urban space, innovation, the consumption of creative ideas in the context of forming regions with "smart cities". In scientific articles, there is a growing popularity of the "smart city" category. Today, this expression is associated with the innovative development of the economy, the creation of prerequisites for the transformation of new knowledge in the practical plane of its implementation and ensure economic and social effect. The institutional basis for obtaining the status of smart cities is the social and creative industries, which are the vector of increasing the innovative potential of the city, and with the reduction of social pressure, transforming the appearance of cities and improving the economic and cultural sense of life of citizens. Results. The emergence of major changes in economic spheres of life are bold in nature, periodically favoring various spheres of economy, sociology, culture, urbanization. Changes also affect the creative approach of cities, as centers of economic life in the region and the state as a whole. This, in turn, influences the need to change the spectrum of regional policy, with the priority of attracting human resources solely with creative thinking and practical approaches to its implementation. Therefore, the social and creative industries should be identified in the positions of the main spheres in which they function in the process of reproduction through the circulation: production, distribution, exchange and consumption. Manufacturing, as the primary sphere of the cycle started, implies a combination of intellectual, innovative and social resources. Conclusions. Exchange determines the process of substitution of monetary compensation for intellectualization and realization of previously created creative results and services, distribution means distribution through various ways and channels of sale of goods and services of creative and social enterprise, and at the last stage of the cycle there is a direct consumption of useful services and services. At the same time, despite the fact that the creative industries, along with science and high technology, are the impetus for an innovative economy, the theoretical and practical studies of this problem are, to say the least, poorly understood. Therefore, creative economy, as a new vector of transformation for meso and macroeconomic systems, requires immediate investigation of this issue.
Keywords: creative industry, smart city, energy efficiency, information and communication sphere, innovative economy, creative economy